Startup accelerators models: the Nova SBE recommendation - Barba, Maria Joana Geraldes (2016)
With an each time more globalized and technological world, opportunities are most of the times around the corner. The courage to take the chance is the first step that should be firmed. To help, there are Startup Acceleration Programs that mentor and support companie’s throughout the beginning of the journey. With a study on worldwide acceleration programs and it’s main future trends, this thesis will build some recommendations on a Pre-acceleration and an Acceleration Program to be developed for the growing entrepreneurial community at NovaSBE.